Beyond Benefiting the Bottom Line: Unpacking the Indirect Effects of Specific CSR Orientations on Work-Life Balance and Engagement - Bachar Kahil (Journal of Advanced Research in Social Sciences and Humanities, 2025)
Aim: The current study aims that CSR dimensions (employees, customers, community, environment and government) significantly impact on work-life balance and work engagement, as well as mediated moderation effects of organizational dehumanization and perceived organizational support among hospitality industry employees in Netherland. Methodology: Drawing with social exchange theory, four-star and five star hotels in the specific Dutch cities of Amsterdam and Rotterdam, data collected 360 employees in hospitality industry and using SmartPLS for data analysis. Findings: The findings shows that organizational dehumanization mediates the relationship among CSR dimensions (employees, customers, community, environment and government) with work-life balance and work engagement. Furthermore, perceived organizational support moderates the relationship on organizational dehumanization with work-life balance and work engagement. Implications/Novel Contribution: The findings emphasize the need for hospitality industry to consider CSR dimensions as a strategic intervention to build the work engagement and work-life balance to bridge the research gap. This study discusses the theoretical and practical implications, policy directions and provides suggestions for future research.